Swiss University Students' Attitudes toward Pharmacological Cognitive Enhancement. - Larissa J Maier; Evangelia Liakoni; Jan Schildmann; Michael P Schaub; Matthias E Liechti (PLoS ONE, 2015)
Pharmacological cognitive enhancement (PCE) refers to the nonmedical use of prescription or recreational drugs to enhance cognitive performance. Several concerns about PCE have been raised in the public. The aim of the present study was to investigate students' attitudes toward PCE. Students at three Swiss universities were invited by e-mail to participate in a web-based survey. Of the 29,282 students who were contacted, 3,056 participated. Of these students, 22% indicated that they had used prescription drugs (12%) or recreational substances including alcohol (14%) at least once for PCE. The use of prescription drugs or recreational substances including alcohol prior to the last exam was reported by 16%. Users of pharmacological cognitive enhancers were more likely to consider PCE fair (24%) compared with nonusers (11%). Only a minority of the participants agreed with the nonmedical use of prescription drugs by fellow students when assuming weak (7%) or hypothetically strong efficacy and availability to everyone (14%). Two-thirds (68%) considered performance that is obtained with PCE less worthy of recognition. Additionally, 80% disagreed that PCE is acceptable in a competitive environment. More than half (64%) agreed that PCE in academia is similar to doping in sports. Nearly half (48%) claimed that unregulated access to pharmacological cognitive enhancers increases the pressure to engage in PCE and educational inequality (55%). In conclusion, Swiss students' main concerns regarding PCE were related to coercion and fairness. As expected, these concerns were more prevalent among nonusers than among users of pharmacological cognitive enhancers. More balanced information on PCE should be shared with students, and future monitoring of PCE is recommended.